More's Utopia - Baker-Smith, Dominic; Renaissance Society of America (Toronto ; Buffalo ; London : University of Toronto Press, 2000)
"Utopia has a strong claim to be the most misunderstood book ever written: its flame has been hijacked by countless idealistic schemes having little in common with More's own assessment of social possibilities. For although it contributes to a line of argument that can be traced from Plato to Marx, Utopia is first and foremost a literary work that appeals to the imagination and seeks to question us rather than to proffer answers." "This study prepares the reader for these challenges, placing the work in the context of early sixteenth-century Europe and the intellectual preoccupations of More's own humanist circle, and clarifying those sources in classical and Christian political thought that provoked his writing." "Utopia is presented as a reflection on political idealism, one that has lost none of its relevance in an age that has witnessed the collapse of Marxist aspirations to social control. Dominic Baker-Smith also surveys the varied critical reception accorded to Utopia over the last four centuries, providing a look at Utopia's role in cultural history."--Jacket
Origins -- "The sceptre of the rulers" -- Platonic satire -- Sanction of custom -- Narrative credentials -- Dialogue of counsel -- Best state of a commonwealth? -- Words and deeds -- In search of Utopia.
Published in association with the Renaissance Society of America.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: More, Thomas, -- Saint, -- 1478-1535.; More, Thomas, -- Sir, saint, -- 1478-1535.; Utopia (More, Thomas, Saint); More, Thomas; POLITICAL SCIENCE -- General; LITERARY CRITICISM -- European -- General; Electronic books; e-books.; Literary criticism; Literary criticism; Livres numériques.; Critiques littéraires.